STRATEGI DINAS PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK, PENGENDALIAN PENDUDUK DAN KELUARGABERENCANA (DP3AP2KB) KABUPATEN SLEMAN DALAM UPAYA MENINGKATKAN KUALITAS HIDUP PEREMPUAN DI KABUPATEN SLEMAN - Endah Neni Miyayi; Hanantyo Sri Nugroho; Ferri Wicaksono; Ardiyati Ardiyati (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Baturaja, 2023)
Optimization of a village is currently being developed a lot that is through changes that were originally a normal village into a deswit (tourist village) which has an attraction to visitors. Usually the development of tourism is implemented in a form that does not eliminate the distinctive characteristics of the activities of the rural community, without replacing the whole but they are still preserving it, both in terms of economic or social culture and utilized overall for the welfare of the people. The Kepuharjo Village Government is currently developing a tourism village, based on regulation No. 23 of 2014 the potential for improving people's welfare is a matter of choice by the government. This encourages each local government to develop a tourist village. The purpose of this research is to understand the application of rules in the framework of developing a tourist village in Kepuharjo, Cangkringan uses the types / types of application of rules according to George C. Edward III. In the preparation of this research researchers used / applied a descriptive qualitative approach. The types of data sources used in this research are primary and secondary data. Based on the results of interviews and observations it can be concluded that the implementation of the tourism village policy in Kepuharjo village is less than optimal. The program implementation is not optimal because there are factors that influence the development of a tourism village, namely the resources and bureaucratic structure, while the driving factors, namely the aspects of communication and disposition.